2022
DOI: 10.3389/fsufs.2022.977841
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping legumes and intermediate wheatgrass increases forage yield, nutritive value, and profitability without reducing grain yields

Abstract: IntroductionKernza intermediate wheatgrass (IWG) is a perennial grain and forage crop. Intercropping IWG with legumes may increase the forage yields and nutritive value but may compromise Kernza grain yields. The interaction between IWG and legumes depends on planting season, row spacing, and legume species. Our aim was to evaluate the effects of those management practices on Kernza grain yield, summer and fall forage yield and nutritive value, weed biomass and, the profitability of the cropping system in Wisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…Avoiding the decline in IWG grain yield in subsequent harvest years remains a major challenge for this perennial crop. Previous research has explored fertilization, row spacing, intercropping, strategic soil disturbance, and postharvest management practices to maintain grain yields but the results are highly variable (Han et al, 2013;Bergquist et al, 2022;Law et al, 2020;Pinto et al, 2021Pinto et al, , 2022Crews et al, 2022).…”
Section: Seasonmentioning
confidence: 99%
See 4 more Smart Citations
“…Avoiding the decline in IWG grain yield in subsequent harvest years remains a major challenge for this perennial crop. Previous research has explored fertilization, row spacing, intercropping, strategic soil disturbance, and postharvest management practices to maintain grain yields but the results are highly variable (Han et al, 2013;Bergquist et al, 2022;Law et al, 2020;Pinto et al, 2021Pinto et al, , 2022Crews et al, 2022).…”
Section: Seasonmentioning
confidence: 99%
“…For example, in Minnesota, Hunter et al (2020b) reported forage mass of 1.0-2.4 Mg ha −1 in the spring, then 1.1-2.8 Mg ha −1 in the fall. Pinto et al (2022) reported ∼1.0 Mg ha −1 of fall forage in Wisconsin. Another Wisconsin study reported spring and fall forage mass approximately equal (1.4 Mg ha −1 ) with the spring relative forage quality values 50% greater than the fall (Favre et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations